Design and Development of Data Processing Applications for Make-Up and Wardrobe Service Orders in Excel Wedding Organizer - Aini Nur Hidayati; Fauziyah Fauziyah; Alexius Ulan Bani (Jurnal Sains dan Teknologi Widyaloka (JSTekWid), 2023)
Data processing of make-up and wardrobe orders on the Excel wedding organizer in its current operations is still done manually, so the admin who wants to process the data still has to record manually on paper, besides that reporting to the CEO also still uses recording in a book. Based on these conditions, this study aims to design and create an information system for data processing of Android-based make-up and wardrobe orders in Excel wedding organizer. The stages of system development in making this information system use the prototyping model method which consists of planning stages, analysis stages, design stages, and implementation stages. Using the Delphi programming language in its manufacture and HeidiSQL as the database. The result of the research is an Android-based make-up and wardrobe data processing information system that assists the admin in processing order data.